“The ideal wife” as “the ideal mother”: some aspects of the Argentinian late eugenic thinking - Miranda, Marisa Adriana (2018)
This work explores some aspects of the eugenic paradigm as a hegemonic thinking in Ar-gentina, its cultural penetration and survival. In this way, that biopolitics consolidation is explained from its immanent imbrication with prevailing ideologies of Liberal-Conservative characteristics. The article concentrates on the weak impact generated by the dissociation between sex, gender, genitality and procreation, which was reasserted since the Sexual Revolution of the Second Post-War period; and, at the same time, in the social root of a marriage concept as locus characterized by a monogamous and lifelong sexual entailment. Here, we hold that this place was conditioned by different influences, as the eugenic normalization of sexuality, which occupied an important site in this field.